PENGARUH CITRA MEREK DAN KUALITAS PELAYANAN DENGAN MINAT MEMAKAI JASA SEBAGAI VARIABEL INTERVENING TERHADAP KEPUTUSAN PEMAKAIAN JASA PENGIRIMAN PAKET PT POS INDONESIA - Rendha Novenda; Wahyu Hidayat; Sari Listyorini (Jurnal Ilmu Administrasi Bisnis, 2013)
This study aimed to determine the effect of brand image and service quality influence by interest usage as intervening variable package shipping service usage decision of PT. Post. Type of research used in this research is explanatory research with 100 respondents taken using purposive sampling techniques. The techinique of analysis used in this study was linear regression with SPSS for windows. The result showed that there were influence of brand image, service quality, and decision of package shipping service usage of PT. Post Indonesia both partially and simultaneously about 61,4% whereas the remain about 38,6% was influenced by other variable which wasn’t inculde within this model